Research on Evaluation Index System of Low-carbon Existing Communities - Wen, Chang; Li, Yang; Zhang, Weiwei; Wang, Guozheng; Li, Bowen; Meng, Sijia (International Journal of Natural Resources and Environmental Studies, 2024)
In recent years, China has carried out urban renewal in an orderly manner. Based on the new stage, to accelerate the construction of a low-carbon innovative society under the urban renewal, we should improve the low-carbon indicator system, deepen the transformation of existing urban communities, and enhance the urban low-carbon innovation capacity. Based on the review and reference of the evaluation system of low-carbon related pilot work, the practice of low-carbon community index system in foreign countries, and the existing research and practice of other Chinese scholars on the existing community low-carbon index system, this paper proposes the construction principles of low-carbon community evaluation index system. This paper summarizes the influencing factor framework of the construction of energy-saving buildings, low-carbon transportation and low-carbon living environment in the process of low-carbon existing communities, and selects the secondary and tertiary indicators according to the influencing factors. A set of low-carbon community index system is proposed to evaluate the existing community, and the operability of the evaluation index system is verified by questionnaire survey